MEMETAKAN RADIKALISME PELAJAR: ANALISIS JARINGAN SOSIAL (SNA) TERHADAP PENGARUH KELOMPOK KEAGAMAAN DI SEKOLAH - Fauzan Azhima (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This article examines the dynamics of radicalism among students through the lens of Social Network Analysis (SNA). The main focus of the research is to map social relationships and the influence of key actors in network-based radicalization processes within school environments. Employing a qualitative case study design, data were collected through snowball sampling, in-depth interviews, participant observation, and analysis of digital documents such as chat groups and religious study materials. The findings reveal that student groups inclined toward radicalism exhibit a small-world network structure that facilitates rapid ideological dissemination. Bridge actors connecting different schools play a crucial role in transmitting exclusive and intolerant religious narratives. Theoretically, the study validates social contagion theory and highlights the relevance of the preferential attachment concept in the formation of radical preaching networks. The practical implications stress the urgency of religious digital literacy training for teachers and the development of SNA-based monitoring systems in schools. However, challenges remain, including limited access to closed networks and potential bias in self-reporting. Therefore, collaboration among educational institutions, deradicalization communities, and security actors is essential to building a resilient educational ecosystem against ideological infiltration.